CALLUS INDUCTION OF CACAO CLONE SULAWESI 1 ON VARIOUS CONCENTRATIONS OF 2,4 -D AND COCONUT WATER VIA IN VITRO CULTURE - Asmila Asmila; Zainuddin Basri; Ramal Yusuf; Hawalina Hawalina (AGROLAND: The Agricultural Sciences Journal, 2017)
Cacao is one of important plantation crops grouped in the Sterculiaceae family.  Sulawesi is the main area of cacao production and has a number of superior clones, such as Sulawesi 1 and Sulawesi 2.  Based on data in 2012/2014 cacao production to consumption reached 174,000 tons, while in 2013/2014 was projected a deficit of 115,000 tonnes. Nonetheless, cacao agribusiness in Indonesia is still facing complex problems, among others gardener productivity is still low due to borer attacks cacao, the quality of products and the number is still low and still not optimal development of cacao products and providing superior amount of cacao seedlings. The primary problem of cacao production recently is low productivity.  The main cause of low cacao productivity in Central Sulawesi is the use of inferior clones.  To enhance cacao productivity, it is crucial to use cacao clones having high genetic potential via tissue culture or micropropagation techniques.  The aim of this experiment was to assess the effect of different concentrations of 2,4-D and coconut water on the growth of cacao callus via in vitro culture.  This experiment used Completely Randomozed Block Design in factorial patteren with treatments tested namely 2,4-D and coconut water concentrations.  The concentrations of 2,4-D tested including 1 ppm, 2 ppm and 3 ppm, whilst coconut water concentrations tested consisting of 10%, 15% and 20%, and therefore there were 3 x 3 = 9 treatment combinations.  Each treatment utilized 4 replications; and each unit combination used 5 explants (staminodia).  Results of this experiment indicated that the addition of 3 ppm 2,4-D and 10% coconut water had a highly significant effect on the callus color 4 weeks after culture.  The addition of 3 ppm 2,4-D in culture media showed a significant effect on callus color 4 weeks after culture, but had an insignificant effect on the callus formation, callus color 8 weeks after culture an callus texture.  Supplementation of 20% coconut water had a significant effect on callus texture 8 weeks after culture, whilst the addition of 10% coconut water showed a significant effect on callus color 4 weeks after culture.